Diagnostic performance of Typhidot RDT in diagnosis of typhoid fever and antibiotic resistance characterisation in a cross-sectional study in Southern Ghana - Emmanuel Kweku Sam; Johnson Alagbo; Avis Asamoah; Felix Ansah; Kwesi Zandoh Tandoh; Lucas N. Amenga-Etego; Samuel Duodu (BMC Infectious Diseases, 2024)
Abstract Background Typhoid fever remains a significant public health problem contributing to significant misapplication of antibiotics in Ghana. However, there is little data on the accuracy of the commonly used serology based rapid diagnostic Typhidot test kit (Typhidot RDT) for confirming typhoid fever. Methods We conducted a study to assess the diagnostic accuracy of Typhidot RDT in seven clinical facilities across five regions in Southern Ghana. A total of 258 participants, clinically diagnosed with typhoid fever, were enrolled in this study. Blood and stool samples were obtained for culture, Typhidot and PCR assays. Disc diffusion antibiotic sensitivity was performed to determine the resistance pattern of Salmonella enterica isolates from positive blood and stool cultures. Results Recovery of S. enterica isolates was higher from stool samples (14.7%) in comparison to blood samples (1.6%). The sensitivity and specificity of Typhidot compared to blood and stool cultures was 35% (19.94%—52.65%) and 45% (38.67%—51.45%), respectively. Compared to PCR, the Typhidot had a sensitivity and a specificity of 61% and 53%, respectively. Resistance phenotyping of isolates showed broad sensitivity to the front-line antibiotics used. Resistance to ampicillin (10%), cotrimoxazole (7%), azithromycin and ciprofloxacin (< 5%) was found in some isolates. Conclusions These findings suggest sub-optimal performance of the Typhidot RDT for diagnosis of typhoid in Ghana with a higher chance for misdiagnosis and misapplication of antibiotics. The high proportion of isolates recovered from stool culture is consistent with the pathophysiology of bacterial shedding during the acute phase of infection, which provides a window of opportunity to control typhoid transmission.